2013
DOI: 10.3389/fpsyg.2013.00250
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between Judgment and Choice of Action in Moral Dilemmas

Abstract: Everyone has experienced the potential discrepancy between what one judges as morally acceptable and what one actually does when a choice between alternative behaviors is to be made. The present study explores empirically whether judgment and choice of action differ when people make decisions on dilemmas involving moral issues. Two hundred and forty participants evaluated 24 moral and non-moral dilemmas either by judging (“Is it acceptable to…”) or reporting the choice of action they would make (“Would you do…… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 35 publications
11
122
2
2
Order By: Relevance
“…over appropriateness of action ("Is it appropriate for you to do it?") because: (i) it tends to be more emotionally arousing 102 , (ii) it tends to elicit more egocentric/self-focused (versus allocentric/other-focused) frame of reference because of potential self-relevant consequences 103 , and (iii) perceived appropriateness of utilitarian course of action on moral dilemmas does not differ in ASD 11 (as compared to healthy controls). Thus, the behavioural choice of action provides a more sensitive measure to tap into moral cognition in autism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…over appropriateness of action ("Is it appropriate for you to do it?") because: (i) it tends to be more emotionally arousing 102 , (ii) it tends to elicit more egocentric/self-focused (versus allocentric/other-focused) frame of reference because of potential self-relevant consequences 103 , and (iii) perceived appropriateness of utilitarian course of action on moral dilemmas does not differ in ASD 11 (as compared to healthy controls). Thus, the behavioural choice of action provides a more sensitive measure to tap into moral cognition in autism.…”
Section: Methodsmentioning
confidence: 99%
“…and found that alexithymia was predictive of acceptability judgments only in controls but not in ASD and concluded that autistics' judgments were based on complying with social rules and were less susceptible to emotional biases. It is possible that these differences stem from emotional saliency of the stimuli used across studies; moral dilemmas involve situations where the individuals have to mull over behavioural choice of directly harming or even killing someone for the benefit of the many and are, thus, inherently highly emotionally evocative 49 , while providing more objective acceptability judgments about emotional sentences may not engage emotional processes to the same extent 102,103 . Another possibility is that there was not enough variation in alexithymia scores in their ASD group to detect an effect (indeed, variance in alexithymia scores in the control group was higher than in the ASD group in the previous study 6 ).…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 99%
“…The observed effects of judgment type and framing underscore how question wording may influence moral judgment (O'Hara, Sinnott-Armstrong, & Sinnott-Armstrong, 2010;Pastötter, Gleixner, Neuhauser, & Bäuml, 2013;Tassy et al, 2013). It is possible that similar wording effects might limit generalizability of other previously found effects on moral judgment and researchers should pay attention to wording effects in future studies to overcome these possible limitations.…”
Section: Discussionmentioning
confidence: 70%
“…That different types of judgment may lead to different moral evaluations was observed in previous studies which showed lower approval of utilitarian actions in case of normative, rather than descriptive judgments 3 (Tassy, Oullier, Mancini, & Wicker, 2013), and lower approval of aggressive retaliation after being provoked in case of prescriptive, rather than descriptive judgments (Goldstein, Tisak, & Boxer, 2002).…”
mentioning
confidence: 76%
“…Some previous experiments on actions in moral dilemmas have asked participants to predict their own behavior (e.g. Bartels, 2008;Petrinovich & O'Neill, 1996;Schaich Borg, Hynes, Van Horn, Grafton, & Sinnott-Armstrong, 2006;Tassy, Oullier, Mancini, & Wicker, 2013). Predictions of behavior have been shown to be notoriously unreliable (Osberg & Shrauger, 1986;Vallone, Griffin, Lin, & Ross, 1990).…”
Section: Introductionmentioning
confidence: 99%